Information design in cheap talk - Qianjun Lyu; Wing-chuen Suen (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
An uninformed sender publicly commits to an informative experiment about an uncertain state, privately observes its outcome, and sends a cheap-talk message to a receiver. We provide an algorithm valid for arbitrary state-dependent preferences that will determine the sender's optimal experiment, and give sufficient conditions for information design to be valuable or not under different payoff structures. These conditions depend more on marginal incentives-how payoffs vary with the state-than on the alignment of sender's and receiver's rankings over actions within a state.
Keywords: 330; marginal incentives; common interest; concave envelope; quasiconcave envelope; double randomization